FAKTOR – FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR - Marwan Marwan; Gerva Upi Pelu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2017)
This research is testing of factors that influencing company capital structure. Profitability (return on assets), asset structure, liquidity (current ratio), firm size (size), and asset growth represent assumed factor have an effect on to measured capital structure use debt equity ratio (DER). Technique of Purposive sampling for the determination of sampel totally population 148 company hence obtained 19 company of sampel totally observation is 95 observation (2009-2013). Data analysis with multilinear regression of ordinary least square. with result of the obtained is Profitability (return on assets) and liquidity (current ratio) having an effect on signifikan to capital structure, while asset structure, company size measure (size), and asset growth do not have an effect on signifikan to company capital structure.